DAMPAK BANJIR AIR PASANG TERHADAP KERUSAKAN LAHAN KOMODITAS PERKEBUNAN DAN PENDAPATAN PETANI DI KECAMATAN KUALA INDRAGIRI KABUPATEN INDRAGI HILIR - Kemas Ramzul Raimi; Eriyati '; Nobel Aqualdo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research was conducted in the district of Kuala Indragiri Hilir Indragiri. The purpose of this study was to determine the impact of land degradation commodities due to tidal flooding and to determine the impact of the flood tide of the income of farmers before and after the flood tide.This study uses a random cluster sampling technique then selected 44 samples. The data used in this research is the primary data and secondary data. Methods of data analysis used in this research is descriptive qualitative and quantitative, qualitative descriptive method done by describing the whole object of research. While descriptive Quantitative namely by displaying a model that systematically as Test Sign (Sign Test). From the research results show that land Plantation Commodity Harm Due Bnjir tide causing losses to farmers. land becomes waterlogged Indragiri River is saltwater. The salt water affect the fruit of his commodities more and shrink, the trunk becomes brittle because of the flood tide is finally easy to fall, the leaves dry out, the land becomes narrower as the tide flooded. muddy plantation land when the floods recede From the research test pins (Sign Test) that Zhitung value smaller than the value Ztabel namely (-6.67 <1.64), which means that H0 is accepted and Ha rejected, which explains that the tide effect on revenue farmers.Keywords: Flood Tide, Estates, Land Degradation, and Revenue.